2008
DOI: 10.1016/j.ijpsycho.2007.10.008
|View full text |Cite
|
Sign up to set email alerts
|

P50 sensory gating and attentional performance

Abstract: Sensory gating refers to the preattentional filtering of irrelevant sensory stimuli. This process may be impaired in schizotypy, which is a trait also associated with cigarette smoking. This association may in part stem from the positive effects of smoking on sensory gating and attention. The relationship among sensory gating, smoking, schizotypy and attention was examined in 39 undergraduates. Sensory gating was indexed by the P50 suppression paradigm, and attention was measured by the Attention Network Test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
67
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 43 publications
8
67
0
2
Order By: Relevance
“…Several studies demonstrated associations between the strength of P50 and performance on attention or detection tasks (Wan et al, 2008;Thomas et al, 2010). P50 has also been shown to play a role in the maintaining of auditory attentive state (Wan et al, 2008). The findings during passive listening are consistent with the hypothesis that Go/NoGo training modified low-level stimulus representations.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Several studies demonstrated associations between the strength of P50 and performance on attention or detection tasks (Wan et al, 2008;Thomas et al, 2010). P50 has also been shown to play a role in the maintaining of auditory attentive state (Wan et al, 2008). The findings during passive listening are consistent with the hypothesis that Go/NoGo training modified low-level stimulus representations.…”
Section: Discussionsupporting
confidence: 62%
“…The decrease in response strength of P50 generators associated with learning to respond to Go stimuli may reflect facilitated access for these stimuli to reach higher processing stages. Several studies demonstrated associations between the strength of P50 and performance on attention or detection tasks (Wan et al, 2008;Thomas et al, 2010). P50 has also been shown to play a role in the maintaining of auditory attentive state (Wan et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In Table 4, the means of amplitudes of the first sound are all larger than the means of amplitudes of the second sound, and the P-values are all less than 0.05. The result of Table 4 is fully consistent with sensory gating [24,[26][27][28].…”
Section: Cognitive Testsupporting
confidence: 80%
“…This function is a mechanism, particularly important for the brain to adapt to new environments, by which the brain filters redundant information and maintains the integrity of cognitive function [24]. Sensory gating protects the cognition by affecting the cognitive processes such as attention and working memory [25].…”
Section: Cognitive Testmentioning
confidence: 99%
See 1 more Smart Citation